CRITERIA OF LEADERSHIP ABILITIES OF FUTURE ECONOMISTS - Hanna Voshkolup (Alfred Nobel University Publisher, 2019)
The article examines the concept of a criterion as an important element in the formation of ideas about a particular phenomenon or process that forms the basis for their assessment, informs the environment about a certain state or phenomenon. It is determined that the phenomenon of leadership has a special place in psychology, since, from a psychological point of view, leadership is expressed in the concrete manifestation of power in human relationships. The lack of unity of opinion of scientists on the formation of a set of criteria for assessing the presence of leadership skills is proved. On the contrary, the arsenal of criteria and indicators is quite diverse. The concept of "criteria for the presence of leadership abilities" is defined as theoretically formed and substantiated signs of the levels of presence and development of leadership skills that are professionally significant in economist's activities, enable an individual to take a leadership position in a team and effectively retain it. It is proved that leadership skills are considered by scientists from two positions. The first focuses on the leadership abilities of the individual in general, as such, helping not only in any professional activity, but also in interpersonal relations (general psychological leadership abilities). The second one determines the leadership abilities of an economist, as a specialist in economics, an entrepreneur, a business owner and invested capital, etc. (professional psychological leadership skills). The scientific views on the formation of general psychological and professional-psychological leadership abilities of future economists are summarized. It is determined that there are a number of leadership abilities belonging to both of the groups that we have identified. At the same time, some scientists attribute them to general psychological ones, while others see them as obligatory in the professional work of economists. In order to eliminate misunderstandings and contradictions in the direction of evaluation, as well as smoothing the influence of the human factor on the formation of criteria for the leadership qualities of economists offered by various scientists, we implemented an expert study of the practical assessment of the manifestation of leadership skills in the environment of specific enterprises. An expert study using the Delphi method was attended by 15 economists working at the leading enterprises of the Dnipropetrovsk region. Their task was to assess the degree of importance (significance) of certain criteria for the presence of leadership abilities in the work of economists. It is determined that experts prefer general psychological leadership abilities, which, according to the averaged calculations, have a significance of 57.5% versus 42.5% for the professional and psychological ones. At the same time, among the general psychological abilities, the most significant ones, according to the experts, were the following: the level of knowledge and intelligence; initiative; self-confidence; persistence, determination, activity; social activity, communicability; the ability to earn trust. Among the professional psychological abilities were: professional knowledge and skills; organizational skills, motivation for group work, ability to defend the interests of the team; delegation of authority, effective planning of their actions and actions of subordinates; consistency in decision making, prioritization, result orientation; adaptability; strategic thinking; initiative and decision-making activity.